On some characteristics of the contemporary Russian-written émigré text (based on Alexander Stesin’s writings) - Посохин, Иван (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
This article discusses various approaches to interpreting Russian-written emigre texts, illustrated through examples from the works of Alexander Stesin (New-Yorkskiy obkhod, Ptitsy zhizni, Troya protiv vsekh). Unlike many of his peers who chose to write in the language of their host country (English), Stesin – a poet and prose writer who emigrated from the USSR as a child – creates his main prose works in Russian. His works often thematize the in-between state and challenges of adaptation faced by a Russianspeaking immigrant in North America. The primary focus of this article is the analysis of the manifestations of a distinct split immigrant identity within Stesin’s literary texts and the identification of exoticization as a semiotic operation in the construction of these texts.